Leadership style in improving innovative work behavior, organizational culture, and organizational citizenship behavior as mediation - Eko Cahyo Purnomo; Roby Sambung; Achmad Syamsudin (Jurnal Inovasi Ekonomi, 2022)
The success of a school is assessed as the success of the principal. The primary key of the principal as an effective leader is to influence and move teachers to participate in every school activity to realize the school's vision and mission. Non-PNS SMK teachers can fulfill all their duties and responsibilities is the answer to the success of a future-oriented leader, having a clear vision and mission, maintaining communication, giving attention, and good relations between leaders and teachers. This study examines and analyzes leadership styles in improving innovative work behavior. The tool used in testing this research uses Smart-PLS.